A Monte Carlo simulation study on the interactions of proton ^7Li and ^12C with water for hadron therapy application - Maratas, Jan Mickelle V. (Transactions of the National Academy of Science and Technology, 2011)
The interactions of ^12C, ^7Li and protons were simulated using a tissue reference media (water). The primary focus is to investigate the nuclear fragmenttion. The primary focus is to investigate the nuclear fragmentation which is believed to be the cause of the so-called dose-tail located right after the Bragg peak structure, which might affect the healthy neighboring tissue of the tutor. Using Monte Carlo Method in GEANT 4 (GEometry And Tracking 4th incarnation) toolkit, a pencil-like beam profile with Gaussian energy distribution is directed towards a box-shaped water target. Mean energies ranging from 100 MeV to 400 MeV for ^12C, 100 MeV to 250 MeV for the ^7Li and 50 to 250 MeV for protons were used. Electromagnetic (EM) interactions are described by the standard and low-energy EM models, while the nuclear fragmentation interactions are described by the Hardonic interaction models such as the Binary cascade and Statistical Multifragmentation Models. Information such as Depth dose profile and peak to entrance ratio were extracted from the simulation. The results show that the peak-to-entrance ratio was longer at higher mean energies for the three projectiles. At 400 MeV the peak-to-entrance ratio was about 3.425 for ^12C. At 250 MeV the peak-to-entrance ratio were 3.615 and 2.514 for protons and ^7Li, respectively. These peak-to-entrance values are approximately half of the highest known value of ^12C at 175 MeV. Unlike protons, ^12C and ^7Li produced a larger dose tail with ^7Li lower by 37.88% than ^12C at 170 mm range. Results suggest that for the three projectiles it is ^7Li which are most suitable for therapeutic radiation therapy since it has lower dose tail compared to ^12C and a more enhanced peak-to-entrance ratio compared to proton.